Show that S2 = S(x,t)S(y,t) solves St = k (Sxx + Syy)(adsbygoogle = window.adsbygoogle || []).push({});

well

St = St(x,t)S(y,t) + S(x,t)St(y,t)

Sxx = Sxx(x,t)S(y,t)

Syy=Syy(y,t)S(x,t)

but what do i do from there?

**Physics Forums | Science Articles, Homework Help, Discussion**

Dismiss Notice

Join Physics Forums Today!

The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

# Diffusion equation in 2d

**Physics Forums | Science Articles, Homework Help, Discussion**